2022
DOI: 10.3390/ijerph191912218
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Students and Medical Residents as Second Victims: A Cross-Sectional Study

Abstract: Background: The term second victim (SV) describes healthcare professionals who remain traumatized after being involved in a patient safety incident (PSI). They can experience various emotional, psychological, and physical symptoms. The phenomenon is quite common; it has been estimated that half of hospital workers will be an SV at least once in their career. Because recent literature has reported high prevalence (>30%) among nursing students, we studied the phenomenon among the whole population of healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Speci cally, legitimizing when they are affected by an experience, when they feel like an SV and when they have the right to use the label. Our ndings are in line with previous studies (13,14,19).…”
Section: Discussionsupporting
confidence: 94%
“…Speci cally, legitimizing when they are affected by an experience, when they feel like an SV and when they have the right to use the label. Our ndings are in line with previous studies (13,14,19).…”
Section: Discussionsupporting
confidence: 94%
“…Students stated that the greatest support comes from their peers, followed by their mentors and, finally, their families and friends [ 32 , 37 39 , 42 , 43 ]. Most hospitals and some universities have support programs specifically tailored for such situations, offering psychological assistance [ 39 ]. However, as these are mostly voluntary aids, many students do not make use of them, and if they do, the support they receive is usually limited.…”
Section: Resultsmentioning
confidence: 99%
“…The study also found that it might be interesting to design interventions for posttraumatic stress disorder (PTSD) for this type of student, as the symptoms of second victims are similar to those of this disorder. Similarly, this study proposes a series of interventions that could be useful, such as psychological therapy, self-help programs, and even drug therapies, as they have been proven effective in treating PTSD [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate the discussion and development of an evidence- and consensus-based definition, A dedicated ERNST working group was launched (WG2). The working group was led by two researchers (KV and MP) with experience of the topic [ 4 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%